Analysis of Guided Inquiry-Based Cladistic E-Worksheet Development to Improve Critical Thinking in High School - Purnamaulida Pratiwi; Topik Hidayat; Amprasto Amprasto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This research aims to analyze the development of Guided inquiry-based cladistic worksheet websites in high schools through that website that has already been developed. The research subjects were 36 students of class X at one of the high schools in Bandung. The research was used by using the experimental method. Students were given Guided inquiry-based cladistic worksheet websites. The instrument used was a Guided inquiry-based cladistic worksheet website, a Feasibility Test by expert lecturers, and a critical thinking test. Critical thinking skill use indicators are Simple Explanation, Conclude, Strategy and Tactics, Building basic skills, Make further explanations. The data were analyzed by using the paired sample T-test. The results showed that the cladistic worksheets based on guided inquiry were valid and effective (N-Gain= 0.54). The assessment analysis by the expert judgment was found to be feasible to be tested in the field without revision, besides that Guided inquiry-based cladistic e-worksheets after validation tests by expert lecturers were obtained from various aspects, such as the application of Guided inquiry to 100% cladistic e-worksheets, practical analysis obtained 91.6%, competency aspect analysis of 91.6%, knowledge construction, obtained a value of 80 and conformity or relevance to KD 100%.  It can be concluded that the development of this media can improve students’ critical thinking skills.